2007
DOI: 10.1001/archpsyc.64.10.1180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Comorbidity of Mental and Physical Conditions on Role Disability in the US Adult Household Population

Abstract: Context: There is limited information that accounts for comorbidity on the impact of role disability associated with a wide range of mental and physical disorders in population-based samples.Objective: To estimate the comparative effects of common mental and physical conditions on role disability in the general population using a novel method that accounts for comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
273
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 413 publications
(294 citation statements)
references
References 52 publications
9
273
1
4
Order By: Relevance
“…Furthermore, though VA has achieved high rates for many preventive services (e.g., cancer screening), delivery of effective behavioral interventions remains a challenge. As primary care is the natural venue for accessing the population that VA serves, PACT provides the optimal platform for quality improvement in mental health across a continuum of condition severity (e.g., from treating uncomplicated depression to identification of severe mental illness) and a locus for attending to the interplay of health behaviors and chronic conditions (e.g., decreased adherence) [9,[13][14][15][16].…”
Section: State Of Affairs Of Mental Health In Primary Care In Va: Thementioning
confidence: 99%
“…Furthermore, though VA has achieved high rates for many preventive services (e.g., cancer screening), delivery of effective behavioral interventions remains a challenge. As primary care is the natural venue for accessing the population that VA serves, PACT provides the optimal platform for quality improvement in mental health across a continuum of condition severity (e.g., from treating uncomplicated depression to identification of severe mental illness) and a locus for attending to the interplay of health behaviors and chronic conditions (e.g., decreased adherence) [9,[13][14][15][16].…”
Section: State Of Affairs Of Mental Health In Primary Care In Va: Thementioning
confidence: 99%
“…20 We are aware of only one population-based US study comparing disability across multiple mental and chronic medical conditions that used a diagnostic instrument to assess mental disorders. 21 This study used days of role impairment as the marker for disability and used statistical simulations to ascribe the relative level of disability to different conditions. The results indicated that mental disorders account for more than half as many days out of role as all chronic medical conditions at the population level.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of mental disorders on early termination of schooling could lead to lifelong decrements in economic and social functioning as well as in the poor health known to be associated with low socio-economic status (Cutler & Lleras-Muney, 2006;Freudenberg et al, 2007;Fronstin, Greenberg, & Robins, 2005;Huurre, Aro, Rahkonen, & Komulainen, 2006;Koivusilta, Rimpela, Rimpela, & Vikat, 2001). As part of a larger investigation of the adverse effects of mental disorders (Merikangas et al, 2007), this study examines associations between early-onset mental disorders and subsequent termination of schooling in a large nationally representative survey of the US adult population. Our aim is to identify the specific disorders associated with termination of 1Corresponding Author: Center for Reducing Health Disparities, Department of Internal Medicine, University of California, Davis, School of Medicine, 2921 Stockton Blvd., Sacramento, CA.…”
mentioning
confidence: 99%